El arquetipo de la madre terrible en el mito de Atis y Cibeles, según José Basileo Acuña. - von Mayer Chaves, Peggy (2012)
This paper analizes the poem from José Basileo Acuña`s book Cantigas de Recreación: "Cuarta Cantiga de Recreación: El Matriarcado y la separación del Hijo". The poet makes an archaetypical-symbolical intepretation of Attys and Cybeles myth, according to Carl G. Jung's Depht Psychology. The outstanding poem explores the archaetype of Terrible Mother, one of the most important fields from Collective Inconscius.